Pengembangan Profesionalisme Guru Pemula dalam Pelibatan Siswa - Dandan Luhur Saraswati; Ari Widodo (Jurnal Penelitian Pendidikan IPA, 2023)
Student involvement is a critical element in effective learning and has a positive impact on the dynamics of the teaching and learning process. This research aims to evaluate the extent to which novice teachers develop their abilities in involving students in learning. The method used was descriptive qualitative research. Research data was collected through three methods namely, observation, interviews, and documentation, all of which were carried out during the implementation of a training program that focused on student engagement techniques. The results of this research conclude that emotional relationships between teachers and students, as well as relationships between students, have a positive effect on students' social and academic development. Apart from that, the level of teacher education also contributes to their level of professionalism, especially in the context of techniques for involving students in learning. These findings emphasize the importance of creating strong emotional bonds between teachers and students and encouraging positive student interactions. In addition, teachers' level of education plays a key role in developing their skills, especially in efforts to engage students effectively in the learning process. This research provides valuable insights into the critical elements influencing teaching quality and teacher professional development.